A Single Imaging Modality in the Diagnosis, Severity, and Prognosis of Pulmonary Embolism. (14th December 2014) - Selimoglu Sen, Hadice; Abakay, Özlem; Cetincakmak, Mehmet Güli; Sezgi, Cengizhan; Yilmaz, Süreyya; Demir, Melike; Taylan, Mahsuk; Gümüs, Hatice
Abstract : Introduction . This study aimed to investigate the currency of computerized tomography pulmonary angiography-based parameters as pulmonary artery obstruction index (PAOI), as well as right ventricular diameters for pulmonary embolism (PE) risk evaluation and prediction of mortality and intensive care unit (ICU) requirement. Materials and Methods . The study retrospectively enrolled 203 patients hospitalized with acute PE. PAOI was calculated according to Qanadli score. Results . Forty-three patients (23.9%) were hospitalized in the ICU. Nineteen patients (10.6%) died during the 30-day follow-up period. The optimal cutoff value of PAOI for PE 30th day mortality and ICU requirement were found as 36.5% in ROC curve analysis. The pulmonary artery systolic pressure had a significant positive correlation with right/left ventricular diameter ratio (r = 0.531, P < 0.001 ), PAOI (r = 0.296, P < 0.001 ), and pulmonary artery diameter (r = 0.659, P < 0.001 ). The patients with PAOI values higher than 36.5% have a 5.7-times increased risk of death. Conclusion . PAOI is a fast and promising parameter for risk assessment in patients with acute PE. With greater education of clinicians in this radiological scoring, a rapid assessment for diagnosis, clinical risk evaluation, and prognosis may be possible in emergency services without the need for echocardiography.